3D Printing of NdFeB Rare Earth Permanent Magnet - Wang Lei; Yan Dingbang; Xie Wei (Advanced Energy Conversion Materials, 2024)
NdFeB (Neodymium magnets) rare earth permanent magnet is an advanced magnetic material characterized by a high energy product and excellent magnetic performance, which has broad application prospects. With the rapid development of 3D printing technology, its application in the research and fabrication of rare earth permanent magnet materials has become a research hotspot. This paper reviews the latest research developments of rare earth permanent magnet NdFeB materials in 3D printing. It introduces the basic properties and applications of rare earth permanent magnet materials and highlights the main challenge these materials faced, which is how do we improve their solid content. Additionally, the advantages and challenges of 3D printing technology in preparing rare earth permanent materials are analyzed in this paper. By comparing the variations in magnet properties of ferrite and rare permanent magnet materials with increasing temperature, it is found that the latter have relatively poor magnetic stability at high temperatures. Based on these points, the paper summarizes optimization methods of the current 3D printing process for rare earth permanent magnet materials. Finally, the paper discusses the development prospects of rare earth permanent magnet materials in 3D printing, as well as problems need to be solved and future research directions.